Improved WASPAS method for determining criteria priority and weights in solving MADM problems: a case study to determine leadership style in Covid-19 pandemic - Mehdi Soltanifar; Seyyed Mohammad Zargar; Maryamsadat Aman (تصمیم گیری و تحقیق در عملیات)
Purpose: The purpose of this research is to provide a hybrid and improved version of one of the Multi-Attribute Decision-Making (MADM) methods, which is a more useful tool for decision support due to the constructive interaction with the decision-maker.Methodology: For this purpose, a linear programming problem with weight restriction and discrimination intensity functions was used to present the improved WASPAS method, and thus, when the explicit weight for the indicators was not taken from the decision maker, it was possible to rank the options.Findings: The results of comparing the use of the proposed method with the WASPAS method showed that this method has a good capability for use in multi-criteria decision making problems and in this particular issue, the results of using this method showed that in the context of the Covid-19 epidemic, the supportive leadership style had the highest rank among the leadership styles, followed by the transactional leadership, participatory, transformational and was placed authoritative.Originality/Value: In this study, the improved WASPAS method was presented to determine the priority and weight of criteria in solving MADM problems and to determine the organizational leadership style in the Covid-19 pandemic.